2009
DOI: 10.1088/0022-3727/42/18/189801
|View full text |Cite
|
Sign up to set email alerts
|

High piezoelectric properties and domain configuration in BaTiO3ceramics obtained through solid-state reaction route

Abstract: The reported data for average grain size g and average domain width w are incorrect in the previously published version. They should be multiplied by a factor of 2. The abstract should therefore be corrected to read as: "... at around 480 nm with the decrease in the grain size from 19 to 4.0 μm." The text on page 3, right column, should read as: line 7: "its g value is 19 μm" line 10: "at g=7 μm" line 20: "at around 480 nm" \noindent line 48: "g values ranging from 19 to 4.0 μm" and on page 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…One is the small grain size. It is known that the dielectric and piezoelectric properties of BT ceramics were maximized at the grain size of ~1 µm, but they decreased with decreasing grain size [4][5][6]. In this study, the grain size was 0.4 µm, therefore the grain size needed to be increased to ~1 µm.…”
Section: Fabrication Of Textured Ceramics Using Mn and Nb-doped Hexagmentioning
confidence: 80%
See 1 more Smart Citation
“…One is the small grain size. It is known that the dielectric and piezoelectric properties of BT ceramics were maximized at the grain size of ~1 µm, but they decreased with decreasing grain size [4][5][6]. In this study, the grain size was 0.4 µm, therefore the grain size needed to be increased to ~1 µm.…”
Section: Fabrication Of Textured Ceramics Using Mn and Nb-doped Hexagmentioning
confidence: 80%
“…There are two major approaches to improving the piezoelectric properties. One is preparation of fine-grained BT ceramics [1][2][3][4][5][6]. It has been reported that the piezoelectric and dielectric properties of BT ceramics were maximized when the grain size was ~ 1 µm [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…183 Several works on BT determine that a fine domain structure can greatly contribute to its piezoelectric activity. [214][215][216][217][218][219][220][221][222] Moreover, charged domains walls were also mentioned as further enhancing the piezoelectricity of materials with fine domains. 223 In general, enhanced electromechanical properties observed in materials with reduced domain size are associated with an increased domain wall density and their enhanced mobility.…”
Section: Grain and Domain Engineeringmentioning
confidence: 99%
“…Recent works demonstrated that exceptionally large electromechanical properties are achievable in pure BT obtained by an engineered synthesis route and/or microstructure. 214,[216][217][218][219][220]222 This compound is formed by relatively stable oxides that led to sintering temperatures around 1500 °C, which is higher than in the other lead-free counterparts. Nevertheless, usually a good sinterability is obtained in this family of materials.…”
Section: Literature Review: Piezoceramics For Actuator Applicationsmentioning
confidence: 99%
“…It is the main component used in different electro-ceramic devices such as Multi-Layer Capacitors (MLCs), ferroelectric memory devices, and also in various applications utilizing its piezoelectric properties [18]. BaTiO 3 (BT) ceramics with a high piezoelectric coefficient have been successfully obtained by the conventional solid-state reaction route starting from ordinary BaCO 3 and TiO 2 powders in the work of Shoufu Shao, Jialiang Zhang et al [19]. It is well known that BT-based electronic devices perform at temperatures less than its Curie temperature (<120 ºC).…”
Section: Introductionmentioning
confidence: 99%